2019
DOI: 10.1002/eap.2039
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and biodiversity co‐benefits of preserving forests in the western United States

Abstract: Forest carbon sequestration via forest preservation can be a viable climate change mitigation strategy. Here, we identify forests in the western conterminous United States with high potential carbon sequestration and low vulnerability to future drought and fire, as simulated using the Community Land Model and two high carbon emission scenario (RCP 8.5) climate models. High‐productivity, low‐vulnerability forests have the potential to sequester up to 5,450 Tg CO2 equivalent (1,485 Tg C) by 2099, which is up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 83 publications
(207 reference statements)
6
78
0
Order By: Relevance
“…Losses in total ecosystem and aboveground C stocks with harvesting generally declined with climatic aridity, in keeping with our second hypothesis. The magnitude of C losses was proportionate to pre-treatment C stocks, as expected (Buotte et al, 2019a). The greatest absolute losses were in the most productive ecosystems and the least in the most arid.…”
Section: Total Ecosystem and Aboveground C Stockssupporting
confidence: 73%
See 3 more Smart Citations
“…Losses in total ecosystem and aboveground C stocks with harvesting generally declined with climatic aridity, in keeping with our second hypothesis. The magnitude of C losses was proportionate to pre-treatment C stocks, as expected (Buotte et al, 2019a). The greatest absolute losses were in the most productive ecosystems and the least in the most arid.…”
Section: Total Ecosystem and Aboveground C Stockssupporting
confidence: 73%
“…The large magnitude difference in both above and belowground C stocks of the humid compared to arid forests, and the greater vulnerability of arid ecosystems to fire and insect disturbances in arid ecosystems (Buotte et al, 2019b), may help inform forest conservation decision-making. Buotte et al (2019a) argue that humid coastal forests with high carbon sequestration capacity, low vulnerability to fire, and high emission potential following harvesting ought to be considered priorities for preservation.…”
Section: Belowground C Stocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Law and colleagues [127] simulated the effect of protecting existing forests, lengthening harvest cycles, re-forestation, afforestation, and bioenergy production with product substitution on net ecosystem carbon balance (NECB) across the state of Oregon and found that lengthening harvest cycles on private land and restricting harvest on public lands resulted in the greatest increases in NECB. Importantly, forest management targeted at preserving high carbon stores can also result in protection of biodiversity [130]. Our study provides additional evidence that forest management in Oregon's productive forests can lead to meaningful statelevel GHG emission reductions.…”
Section: Plos Onementioning
confidence: 68%